“Classical Antiquity” in Sergei G. Stroganoff’s Grand Cabinet: A Case of Reconstruction after the Photo by Giovanni Bianchi (1865) - Semenova, Yulia G.; Terentieva, Irina O. (Actual Problems of Theory and History of Art, 2018)
The Stroganov family collection of art, the greater part of which entered the Hermitage after the October Revolution, is known both for its diversity and high artistic level. Among its items there are objects acquired by Count Sergei Grigorievich, who was considered to be an expert in Classical antiquity as well as in other ancient works of art. “Antiques” from his collection are now held by the Department of Greek and Roman Antiquities at the State Hermitage Museum, and are well known to specialists.The Stroganov family collection of art, the greater part of which entered the Hermitage after the October Revolution, is known both for its diversity and high artistic level. Among its items there are objects acquired by Count Sergei Grigorievich, who was considered to be an expert in Classical antiquity as well as in other ancient works of art. “Antiques” from his collection are now held by the Department of Greek and Roman Antiquities at the State Hermitage Museum, and are well known to specialists.In the article, based on visual sources, an attempt is made to recreate the Count’s personality as a collector and understand his artistic preferences. The authors particularly rely upon the photographs of the interiors at the Stroganov Palace, taken by I. K. Bianchi in 1865, and currently kept in the photographic collection of the Department of the History of Russian Culture at the State Hermitage Museum. The authors also draw attention to Count’s photographic collections of which little is known in comparison with other objects from the Stroganov collection.
Keywords: art of Classical antiquity; antique art objects; Apollo; Grand Tour; view photographs; Stroganov Palace’s interiors; Italy; collecting; Stroganov collections; Rome; Forum Romanum; Stroganov palaces; the Stroganovs; photographer J. C. Bianchi; photographer Tommaso Cuccioni; photography; photo reproductions; The State Hermitage Museum